A Novel CCM2 Missense Variant Caused Cerebral Cavernous Malformations in a Chinese Family - Han, Guoqing; Ma, Li; Qiao, Huanhuan; Han, Lin; Wu, Qiaoli; Li, Qingguo (Frontiers in Neuroscience, 2021)
Cerebral cavernous malformations (CCMs) are common vascular malformations in the central nervous system. Familial CCMs (FCCMs) are autosomal dominant inherited disease with incomplete penetrance and variable symptoms. Mutations in the KRIT1, CCM2, and PDCD10 genes cause the development of FCCM. Approximately 476 mutations of three CCM-related genes have been reported, most of which were case reports, and lack of data in stable inheritance. In addition, only a small number of causative missense mutations had been identified in patients. Here, we reported that 8/20 members of a Chinese family were diagnosed with CCMs. By direct DNA sequencing, we found a novel variant c.331G > C (p.A111P) in exon 4 of the CCM2 gene, which was a heterozygous exonic variant, in 7/20 family members. We consider this variant to be causative of disease due to a weaken the protein–protein interaction between KRIT1 and CCM2. In addition, we also found the exon 13 deletion in KRIT1 coexisting with the CCM2 mutation in patient IV-2, and this was inherited from her father (patient III-1H). This study of a Chinese family with a large number of patients with CCMs and stable inheritance of a CCM2 mutation contributes to better understanding the spectrum of gene mutations in CCMs.